KONSTRUKSI LAPORAN KEUANGAN PONDOK PESANTREN (STUDI PADA PONDOK PESANTREN AL-WASHOYA JOMBANG) - Istutik; Isnaini Putri Rahmawati; Hedher Tuakia (Jurnal Manajemen Dirgantara, 2023)
Pondok Pesantren is an Islamic Boarding School as a non-profit organization in the field of education carries out its activities with resources from the community. Transparency of financial reports is the main thing in accountability to stakeholders, especially external parties. Financial reports are prepared and presented in such a way that they are understandable and relevant to the needs of users of financial statements in making decisions. This case study research at the Al-Washoya Islamic Boarding School, Jombang resulted in the construction of its financial statements based on ISAK 35 and Islamic Boarding School Accounting Guidelines. The implementation of ISAK 35 and the Islamic Boarding School Financial Accounting Guidelines is carried out so that the presentation of the Al-Washoya Jombang Islamic Boarding School report as a non-profit concern organization pays attention to the requirements for presenting financial statements, the structure of financial reports and the minimum requirements for the contents of financial reports.